Shallow slow slip events identified offshore the Osa peninsula in Southern Costa Rica from GNSS time series - Perry, Mason (2023)
Using new continuous geodetic time series, we identify five shallow slow slip events (SSEs) offshore and beneath the Osa peninsula in southern Costa Rica. An early event was detected by one station in 2013, and two events occurring in close succession in both 2018 and 2022 were detected by multiple stations, indicating a preliminary recurrence interval of ~4-5 years. While SSEs have been observed to the northwest at Nicoya, this is their first documentation in southern Costa Rica. Modeled slip distributions of the 2018 and 2022 events indicate they likely ruptured the same or overlapping patches of the plate interface, near the trench, updip of the 1983 Mw 7.4 Osa event. Immediately offshore, estimated cumulative slip from the 2018 and 2022 events is sufficient to close the slip deficit from tectonic loading over the recurrence interval, potentially limiting the magnitude and spatial slip distribution of future large ruptures.